Cucurbit[7]uril as a catalytic nanoreactor for one-pot synthesis of isoxazolidines in water. Issue 6 (29th January 2020) - Gentile, Davide; Floresta, Giuseppe; Patamia, Vincenzo; Nicosia, Angelo; Mineo, Placido G.; Rescifina, Antonio
Abstract : The main objective of supramolecular chemistry is to mimic the macrosystems present in nature, a goal that fits perfectly with the green chemistry guidelines. Abstract : The main objective of supramolecular chemistry is to mimic the macrosystems present in nature, a goal that fits perfectly with the green chemistry guidelines. The aim of our work is to use the hydrophobic cavity of cucurbit[7]uril (CB[7]) to mimic nature for performing different dehydration and cycloaddition reactions in water. The hydrophobic cavity of CB[7] made it possible to synthesize nitrones and isoxazolidines in a one-pot fashion using water as a reaction solvent. Substituted isoxazolidines were obtained from the cycloaddition of nitrones with various styrenes and cinnamates, under microwave irradiation, with a catalytic amount of CB[7], and a moderate increase in the formation of the trans adduct was observed, compared to the reaction being carried out in toluene. The mechanism of the reaction and the inclusion of reagents and products in the CB[7] cavity have been studied and rationalized by NMR spectroscopy, ESI-MS experiments, and molecular modeling calculations.